Annealing of RF-magnetron sputtered SnS2 precursors as a new route for single phase SnS thin films - Sousa, M.G. (2019)
Tin sulphide thin films have been grown on soda-lime glass substrates through the annealing of RF-magnetron sputtered SnS2 precursors. Three different approaches to the annealing were compared and the resulting films thoroughly studied. One series of precursors was annealed in a tubular furnace directly exposed to a flux of sulphur vapour plus forming gas, N2 + 5%H2, and at a constant pressure of 500 mbar. The other two series of identical precursors were annealed in the same furnace but inside a graphite box with and without elemental sulphur evaporation again in the presence of N2 + 5%H2 and at the same pressure as for the sulphur flux experiments. Different maximum annealing temperatures for each set of samples, in the range of 300–570 C, were tested to study their effects on the properties of the final films. The resulting phases were structurally investigated by X-Ray Diffraction (XRD) and Raman spectroscopy. Annealing of SnS2 precursors in sulphur flux produced films where SnS2 was dominant for temperatures up to 480 C. Increasing the temperature to 530 C and 570 C led to films where the dominant phase became Sn2S3. Annealing of SnS2 precursors in a graphite box with sulphur vapour at temperatures in the range between 300 C and 480 C the films are multi-phase, containing Sn2S3, SnS2 and SnS. For high annealing temperatures of 530 C and 570 C the films have SnS as the dominant phase. Annealing of SnS2 precursors in a graphite box without sulphur vapour at 300 C and 360 C the films are essentially amorphous, at 420 C SnS2 is the dominant phase. For temperatures of 480 C and 530 C SnS is the dominant phase but also same residual SnS2 and Sn2S3 phases are observed. For annealing at 570 C, according to the XRD results the films appear to be single phase SnS. The composition was studied using energy dispersive spectroscopy being then correlated with the annealing temperature. Scanning electron microscopy studies revealed that the SnS films exhibit small grain structure and the film surface is rough. Optical measurements were performed, from which the band gap energies were estimated. These studies show that the direct absorption transitions of SnS are at 1.68 eV and 1.41 eV for annealing in graphite box with and without elemental sulphur evaporation, respectively. For the indirect transition the values varied from 1.49 eV to 1.37 eV. The results of this work show that the third approach is better suited to produce single phase SnS films. However, a finer tunning of the duration of the high temperature plateau of the annealing profile is required in order to eliminate the b-Sn top layer.